Estudio de la corrosión atmosférica del cobre en la ciudad de Cartagena de Indias durante el primer año de exposición (2024)
This investigation evaluates the rate of copper corrosion in the city of Cartagena de Indias in the first year of exposure. Samples of the material were exposed in 2 sites of the city, Universidad Antonio Nariño and Universidad Mayor de Cartagena (UAN and Mayor), the corrosion rate was determined by the method of mass loss and dose-response function, and a subsequent evaluation of the material was carried out by means of electrochemical impedance. polarization curves and scanning electron microscopy.